The Changing Character of the Christian International - Cordova, Efren (Relations industrielles / Industrial Relations, 1968)
It can hardly be doubted that the International Federation of Christian Trade Unions has undergone a profound transformation. Not only has it ceased to be an exclusively European movement, but it is rapidly growing secular and also becoming a radical or revolutionary type of trade unionism.